2011
DOI: 10.1021/jp2019236
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Reactivity on the C7H6 Potential Energy Surface

Abstract: The reactivity and decomposition kinetics on the C(7)H(6) potential energy surface (PES) were investigated, determining structures of stationary points at the B3LYP/6-31+G(d,p) level and energies at the CCSD(T)/cc-pVTZ level with extension to the complete basis set limit. For the reactions characterized by a significant multireference character, the energies were calculated at the CASPT2/cc-pVTZ level. The portion of the PES investigated consisted of 27 wells connected by 39 saddle points. Of the 27 wells, 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 81 publications
(138 reference statements)
2
44
0
Order By: Relevance
“…Several test calculations showed that relative energies on the C 10 H 11 PES computed through eq 1 are comparable within 1.5 kcal/mol with those determined with CCSD(T) energies extrapolated to the CBS limit using the much more computationally expensive cc-pVDZ/cc-pVTZ extrapolation scheme we recently adopted to investigate the C 7 H 6 PES. 31,32 To improve the level of accuracy of the calculations, the energies of the saddle points whose reaction fluxes are rate determining were also calculated using the ROCBS-QB3 methodology proposed by Wood et al 33 This computational approach was designed to improve the level of accuracy of reaction energies calculated using the CBS-QB3 approach when spin contamination is relevant, thus eliminating the need to include the CBS-QB3 empirical corrections factor for spin contamination. This is accomplished by performing the calculations using spin restricted wave functions.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Several test calculations showed that relative energies on the C 10 H 11 PES computed through eq 1 are comparable within 1.5 kcal/mol with those determined with CCSD(T) energies extrapolated to the CBS limit using the much more computationally expensive cc-pVDZ/cc-pVTZ extrapolation scheme we recently adopted to investigate the C 7 H 6 PES. 31,32 To improve the level of accuracy of the calculations, the energies of the saddle points whose reaction fluxes are rate determining were also calculated using the ROCBS-QB3 methodology proposed by Wood et al 33 This computational approach was designed to improve the level of accuracy of reaction energies calculated using the CBS-QB3 approach when spin contamination is relevant, thus eliminating the need to include the CBS-QB3 empirical corrections factor for spin contamination. This is accomplished by performing the calculations using spin restricted wave functions.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Density functional theory (DFT) calculations 14 found that hydrogen addition to fulvenallene would result in C 5 H 5 + C 2 H 2 . Recently, there has been extensive work [15][16][17][18][19] performed on potential energy surfaces for each of the species C 7 H 7 , C 7 H 6 , and C 7 H 5 and their interplay during benzyl radical decomposition. Because of their likely importance during the decomposition of benzyl, both fulvenallene and fulvenallenyl radicals, 20,21 as well as the cycloheptatrienyl radical 22 have been detected and identified by PIMS.…”
Section: Figmentioning
confidence: 99%
“…The correlation consistent double and triple z basis sets cc-pVDZ and cc-pVTZ were used for all CCSD(T) calculations, which allowed to extrapolate the energies to the complete basis set limit (CBS) adopting the scaling coefficient suggested by Martin and including the zero point energy (ZPE) corrections calculated at the B3LYP/6-31+G(d,p) level. 37,43 Among the elementary reactions investigated, the dissociation of the 2-methylphenyl radical into methyl and benzyne does not have a saddle point. Its potential energy surface was thus determined as a function of the reaction coordinate, defined as the length of the breaking bond, with steps of 0.05 A ˚starting from a C-C distance of 2.5 A ˚.…”
Section: Ab Initio and Dft Calculationsmentioning
confidence: 99%
“…20 To improve our understanding of the fulvenallene reaction channel we have recently investigated the reactivity on the C 7 H 6 PES using both ab initio calculations performed at the CCSD(T) level on B3LYP/6-31+G(d,p) structures using cc-pVDZ and cc-pVTZ basis sets and extrapolating the energies to the complete basis set. 37 The C 7 H 6 decomposition kinetics was successively examined by integrating the master equation (ME). 38 It was found that in addition to decomposing to the fulvenallenyl radical (C 7 H 5 ) and atomic hydrogen, as suggested by da Silva and Bozzelli, 39 fulvenallene can also decompose to acetylene and the cyclopentadienylidene di-radical (cC 5 H 4 ).…”
Section: Introductionmentioning
confidence: 99%